2015
DOI: 10.1021/la504651v
|View full text |Cite
|
Sign up to set email alerts
|

Size Effects in MgO Cube Dissolution

Abstract: Stability parameters and dissolution behavior of engineered nanomaterials in aqueous systems are critical to assess their functionality and fate under environmental conditions. Using scanning electron microscopy, transmission electron microscopy, and X-ray diffraction, we investigated the stability of cubic MgO particles in water. MgO dissolution proceeding via water dissociation at the oxide surface, disintegration of Mg(2+)-O(2-) surface elements, and their subsequent solvation ultimately leads to precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 48 publications
4
67
0
1
Order By: Relevance
“…The XRD pattern of the synthesized MgO is shown in Figure 2a [20]. The crystallite size is determined using Scherrer's formula, d = 0.9 /ˇ cos Â, where d is the crystallite size, is wavelength of X-ray radiation, ˇ is full width at half maximum and  is the diffraction angle.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD pattern of the synthesized MgO is shown in Figure 2a [20]. The crystallite size is determined using Scherrer's formula, d = 0.9 /ˇ cos Â, where d is the crystallite size, is wavelength of X-ray radiation, ˇ is full width at half maximum and  is the diffraction angle.…”
Section: Resultsmentioning
confidence: 99%
“…Work by Sutcu et al (2009) showed that the (1 1 1) crystal face of MgO particles was most susceptible to hydration by exposure to water vapor and a relative humidity of 88% in the cited work. Research by Baumann et al (2015) has shown that the rate of dissolution of MgO particle increases with their decreasing size, and that dissolution takes place more slowly if a stable layer of Mg(OH)2 has formed on the particle surfaces.…”
Section: Assumed Chemical Reactions In Non-aqueous Dispersion Treatmentmentioning
confidence: 99%
“…Furthermore, consistent with the crystallite domain size the particle sizes, as determined by TEM analysis, remain in the range below 10 nm. 19 Irrespective from the retained primary particle properties, the agglomerates have become more compact (upper micrographs of Fig. 5a and b) in comparison to MgO nanocube powders before functionalization (Fig.…”
Section: Spontaneous Ber Growthmentioning
confidence: 98%
“…Subsequently, the temperature is raised to 1173 K and, at pressures of p < 5 Â 10 À6 mbar, kept at this temperature for 1 h before cooling to room temperature. 19 As revealed by Transmission Electron Microscopy CVS MgO consists of highly dispersed monocrystalline nanocubes with a high portion of edge and corner features (Fig. S1a, ESI †).…”
Section: Chemical Vapor Synthesis Of Mgomentioning
confidence: 99%
See 1 more Smart Citation